Linguistic Risk-Taking: A New Pedagogical Approach and a Research Program - Slavkov, Nikolay (Canadian Journal of Applied Linguistics / Revue canadienne de linguistique appliquée)

(untitled) (University of New Brunswick, 2023)
Linguistic risks are situations in which learners are pushed out of their comfort zone to use the target language in meaningful and authentic settings. This article outlines a novel pedagogical and research approach to language learning through linguistic risk-taking. I review the construct of linguistic risk from interdisciplinary perspectives and describe the context, rationale, and development of an innovative initiative for supporting French and English language learning at the University of Ottawa, the largest bilingual (English-French) university in the world. Data from 554 participants collected through a Linguistic Risk-Taking Passport, a tool allowing learners to self-report risk-taking patterns, propose additional risks, and add qualitative comments are analyzed to validate the approach. Avenues for transformation of the tool into a digital app and its relevance to other contexts and other languages are also discussed.